2018
DOI: 10.1016/j.physbeh.2017.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Correlated colour temperature of morning light influences alertness and body temperature

Abstract: Though several studies have reported human alertness to be affected by the intensity and spectral composition of ambient light, the mechanism behind this effect is still largely unclear, especially for daytime exposure. Alerting effects of nocturnal light exposure are correlated with melatonin suppression, but melatonin levels are generally low during the day. The aim of this study was to explore the alerting effect of light in the morning for different correlated colour temperature (CCT) values, as well as it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 36 publications
2
39
0
1
Order By: Relevance
“…Studies measuring physiological signals and perceived comfort showed that visual discomfort was higher under 6500 K of light compared with 2700 K for LED lights and the illuminances of S cones and melanopsin for 6500 K increased about 244% and 136%, respectively, which agrees with our findings. However, other studies using fluorescent lights that measured physiological signals showed that blue‐enriched light (6000 vs 2700 K) had no effects on comfort experience .…”
Section: Discussionsupporting
confidence: 91%
“…Studies measuring physiological signals and perceived comfort showed that visual discomfort was higher under 6500 K of light compared with 2700 K for LED lights and the illuminances of S cones and melanopsin for 6500 K increased about 244% and 136%, respectively, which agrees with our findings. However, other studies using fluorescent lights that measured physiological signals showed that blue‐enriched light (6000 vs 2700 K) had no effects on comfort experience .…”
Section: Discussionsupporting
confidence: 91%
“…It agreed with that the visual acuity dropped off seriously and the symptom of dry eyes was more acute after the exposure of blueenriched white light. Studies measuring physiological signal and perceived comfort showed that visual comfort was higher under 2700K light compared with 6500K for LED lights [9]. The illuminances of S cones and melanopsin increased about 244% and 136% respectively for 6500K, and the result was agreed with ours.…”
Section: -5 / Y Zhangsupporting
confidence: 88%
“…The current manuscript focuses on the interactions between the perception of light exposure and the perception of ambient temperature. Results of these studies on the alerting effects of light in relation to thermophysiological parameters (body temperatures) are reported elsewhere . The study design of both experiments was similar, consisting of two sessions with three time blocks with different ambient temperatures.…”
Section: Methodsmentioning
confidence: 99%
“…Results of these studies on the alerting effects of light in relation to thermophysiological parameters (body temperatures) are reported elsewhere. 17,18 The study design of both experiments was similar, consisting of two sessions with three…”
Section: Me Thodmentioning
confidence: 99%